Impact of climate change research at a South African tertiary institution: Monitoring and evaluating research dissemination and policy influence using Altmetric and Overton - de Bruyn, Melanie; van Niekerk, Johan; Venter, Sonja (Technium Social Sciences Journal, 2025)
Climate change is currently a main focus of many research related projects. It is important to monitor and evaluate the impact of this research to understand its dissemination and contribution. This study made use of two online platforms, Altmetric and Overton, to determine the academic, social and policy impact of climate change research associated with a South African tertiary institution. Comparisons between the two platforms and types of impact were made using correlations and paired t-tests. Results showed a high academic and policy impact, with lower online social attention. Online social impact did not predict academic impact however, a three-year delay was identified between online attention and policy inclusion. Findings suggested that research was disseminated and engaged with among many sectors and subject areas, highlighting an interdisciplinary impact resulting in real-world solutions.